Consumer perceived risk in online shopping environment via Facebook as medium - Panwar, Charu (International Journal of Engineering and Technology, 2018)
The study aims to understand the consumer buying behavior while shopping online. The study unveils the multidimensional perceived risk in online shopping that will be helpful for the marketers in mitigating the perceived risk. The study used universally accepted determinants of consumersâ€™ perceived risk namely financial risk, product risk, delivery risk, time risk and privacy risk. This multi-pronged perceived risk has significant impact on the online shopping behavior of the customer and adversely affects their purchase behavior. The total number of 180 respondent has been selected for the primary study. The convenient sampling method of non-probability sampling has been used for selection of respondents. The study found that the demographics have a major role to play on consumersâ€™ perception towards online shopping. Income and gender are the two important factors identified that may have considerable impact on consumersâ€™ perception towards online shopping. T-test, ANOVA and regression analysis has been used for data analysis purpose.Â